PENGARUH PERMENDIKBUD NOMOR 30 TAHUN 2021 TERHADAP SEBARAN KASUS PELECEHAN SEKSUAL (Kafa`ah: Journal of Gender Studies, 2022)
The large number of cases of sexual harassment in Indonesia makes people feel restless in dealing with this issue. Especially in the world of education at the university level, there are many cases of sexual harassment experienced by several students. They are harassed in the campus environment which is carried out between lecturers and students or students with students, so that it disturbs the concerns of other students to carry out education in the campus environment. Therefore, the Minister of Education, Culture, Research and Technology Nadiem Makarim issued Regulation of the Minister of Education, Culture, Research, and Technology No. 30 of 2021 concerning the Prevention and Handling of Sexual Violence which was just inaugurated on August 31, 2021. Therefore, I conducted a survey by distributing questionnaires to be filled out by the general public and students, especially students to find out whether they understand and the impact of this regulation on the distribution of cases of sexual harassment in Indonesia. Many of them said that sexual harassment on campus was immoral and set a bad example for others. Such action is also a violation of Human Rights. Victims of these actions are generally afraid to report the incident that happened to them to the authorities due to pressure from the campus with frills to maintain the good name of the campus. However, the existence of this binding regulation provides legal protection for victims so that they dare to report acts of sexual harassment within the campus. Many people have the opinion that this binding regulation has a big impact on victims and universities, because the existence of this binding regulation is able to reduce acts of sexual harassment that occur within the campus.